Mucin 21 is a novel, negative immunohistochemical marker for epithelioid mesothelioma for its differentiation from lung adenocarcinoma. Issue 4 (15th January 2019) - Kai, Yuichiro; Amatya, Vishwa J; Kushitani, Kei; Kambara, Takahiro; Suzuki, Rui; Tsutani, Yasuhiro; Miyata, Yoshihiro; Okada, Morihito; Takeshima, Yukio
Abstract : Aims: The process of differential diagnosis between epithelioid mesothelioma and lung adenocarcinoma has been progressing; however, there are no absolute immunohistochemical markers with which to definitively diagnose epithelioid mesothelioma. The aim of this study was to search for a novel negative marker of epithelioid mesothelioma. Methods and results: We immunohistochemically studied the applicability of mucin 21 (MUC21), which was identified in our previous study, as a novel, negative diagnostic marker for epithelioid mesothelioma. Seventy epithelioid mesotheliomas and 70 lung adenocarcinomas were investigated for the expression of MUC21, along with other previously reported markers, by the use of immunohistochemistry. MUC21 was expressed in only two of the 70 (3%) epithelioid mesotheliomas, as compared with 67 of the 70 (96%) lung adenocarcinomas. The sensitivity, specificity and accuracy of negative MUC21 expression for differentiating epithelioid mesothelioma from lung adenocarcinoma were 97%, 96%, and 96%, respectively; these are similar to those of carcinoembryonic antigen and claudin‐4, and better than those of thyroid transcription factor‐1, napsin‐A, and mucin 4. Conclusion: MUC21 could be used as an additional, novel, negative immunohistochemical marker to differentiate mesothelioma from lung adenocarcinoma.